Risiko dominan di Perbankan Syariah: Pembiayaan, pasar, likuiditas, dan operasional - Vinori, Jafria (Maliki Interdisciplinary Journal, 2024)
Everyday activities are not free from risks, the same goes for the banking sector, especially sharia banks. Even with the variety of risks in sharia banking, it is necessary to implement risk management for sharia banks. This is done because with risk management, you can identify risks, measure each risk and then resolve (solve) the risks that will be or are being faced. Don't forget that the risk management principles used by sharia banking in Indonesia are implemented in line with the standard rules issued by the IFSB (Islamic Financial Services Board).